1989
DOI: 10.1104/pp.90.2.686
|View full text |Cite
|
Sign up to set email alerts
|

Use of Per-C-Deuterated myo-Inositol for Study of Cell Wall Synthesis in Germinating Beans

Abstract: Coll wall polysaccharides of the hypocotyl and roots in germinating beans (Phaseolus vulgaris L.) were selectively labeled in arabinosyl, xylosyl, and galacturonosyl residues by per-C-deuter-ated myo-inositol, which was introduced through 72 hours of imbibition. Glucuronate residues remained unlabeled. Selected ion gas chromatography-mass spectrometry analysis revealed that deuterium was not redistributed in these three sugar residues or into other carbohydrate residues during this conversion, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Unlike procedures utilizing 2H- (Sasaki et al 1989) or ~3C-labeled sugars (Greve and Labavitch 1991), in which the choice of substrate may influence the distribution of label, sugars were labeled in proportion to their abundance with the 13C02 method.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike procedures utilizing 2H- (Sasaki et al 1989) or ~3C-labeled sugars (Greve and Labavitch 1991), in which the choice of substrate may influence the distribution of label, sugars were labeled in proportion to their abundance with the 13C02 method.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of the label (and, thus, incorporation into the wall) is accomplished by means of a GC-MS analysis which compares the isotope ratio of selected ion pairs from individual monosaccharide residues. This method is similar to the technique of Sasaki et al (18) who examined the fate of density-labeled inositol in the cell walls of germinating beans but is useful for the analysis of a greater range of monosaccharides because of the more general distribution of carbon from glucose into other sugars. The technique can also be applied to permethylated samples of cell wall polysaccharides and thus provide information regarding incorporation into specific cell wall polymer types.…”
mentioning
confidence: 99%
“…Myo-inositol is also considered as a growth enhancer in vitro and may be a carbohydrate source, which are good osmoticum for protoplast isolation (Azad et al 2006). Myo-inositol oxidation pathway has a predominant role in the biosynthesis of new cell walls of the hypocotyl and roots in germinating beans (Sasaki et al 1989). Recently, Abid et al (2009) reported that myo-inositol phosphate synthase (MIPS), which catalyses the first step in inositol biosynthesis are involved in various physiological processes including embryogenesis, seedling growth and resistance to biotic and abiotic stresses.…”
Section: Effect Of Growth Regulators On Cell Division Of Cabbage Protmentioning
confidence: 99%